The Sustainable Development: A Path to Economic Development in Iraq - Khalaf, Qasim Jabbar; Faraj, Sakinah Jahiya (PT Inovasi Pratama Internasional, 2025)
This study explores the evaluation of the impact of sustainability practices on the economic indicators of countries. The research sample consists of 200 individuals, including professors and students from the College of Economics at the University of Baghdad, serving as the basis for collecting the necessary data to measure the research variables. The methodology employs a mixed approach, combining quantitative data from questionnaires with secondary data from national and international reports. The most significant results indicate that sustainable development practices, such as improving certain environmental practices, investing in renewable energy, and enhancing education and health, support economic indicators. The study recommends establishing a comprehensive development strategy, increasing investment in renewable energy, and promoting innovation and economic diversification.